Optimal design on the mechanical and thermal properties of porous alumina ceramics based on fractal dimension analysis. Issue 3 (25th December 2017) - Liu, Jingjing; Li, Yuanbing; Yan, Shu; Zhang, Zaijuan; Huo, Wenlong; Zhang, Xiaoyan; Yang, Jinlong
Abstract: In order to investigate the relationship between pore structure and thermal conductivity as well as mechanical strength, porous alumina ceramics (PAC) with various pore structures were fabricated, using starch as the pore‐forming agent. Fractal theory was employed to characterize the pore size distribution more accurately than ever used parameters. The results show that the increase in starch content in PAC leads to an enhanced porosity, a higher mean pore size, and reduced fracture dimension, thermal conductivity and strength. The fractal analysis indicated that the fractal dimension decreases gradually and reaches its minimum value with increasing the starch content up to 25 wt%, but the further incorporation results in an opposite trend. It is suggested from micro‐pore fractographic analysis that the optimization of both thermal insulation performance and mechanical strength are positively correlated with the increase in the mean pore size and proportion of 2‐14 μm pores but negatively corrected with the porosity. These results provide a new perspective and a deeper understanding for fabrication of PAC with both excellent thermal insulation and mechanical performance.